Shakespeare. - Herder, Johann Gottfried (Princeton University Press, 2011)
Without Johann Gottfried Herder (1744-1803), we simply would not understand Shakespeare in the way we do. In fact, much literature and art besides Shakespeare would neither look the same nor be the same without the influence of Herder's "Shakespeare" (1773). One of the most important and original works in the history of literary criticism, this passionate essay pioneered a new, historicist approach to cultural artifacts by arguing that they should be judged not by their conformity to a set of conventions imported from another time and place, but by the effectiveness of their response to their.